2013
DOI: 10.7753/ijsea0201.1001
|View full text |Cite
|
Sign up to set email alerts
|

Medium optimization for production of L-Glutaminase (EC 3.5.1.2) by Streptomyces griseus under submerged fermentation

Abstract: L-Glutaminase is widely distributed in microorganisms including bacteria, yeast and fungi. The enzyme mainly catalyzes the hydrolysis of γ-amido bond of l-glutamine. In this report medium optimization was conducted through one -factor -at -a -time approach for the submerged production of L-Glutaminase by Streptomyces griseus using different additional carbon, nitrogen, amino acids, mineral salts and was treated with different concentration sodium chloride. A significant influence of medium components (g/l) Gal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Overall, all carbon sources did not exhibited much significant increase in L-glutaminase production due to Dox modify medium free carbon relatively yielded a high amount of L-glutaminase (119.64 U/ml). On the contrary, the yield of L-glutaminase from S. griseus was increased to 26.3 U/ml by utilized the galactose as the carbon source [47]. Table 4 showed effect lysine, isoleucine, glycine, thiamine, arginine, treptophan, proline, glutamic acid, cysteine, andmethionine on L-glutaminase production.…”
Section: Effect Of Different Nitrogen and Carbon Sources On L-glutamimentioning
confidence: 99%
See 2 more Smart Citations
“…Overall, all carbon sources did not exhibited much significant increase in L-glutaminase production due to Dox modify medium free carbon relatively yielded a high amount of L-glutaminase (119.64 U/ml). On the contrary, the yield of L-glutaminase from S. griseus was increased to 26.3 U/ml by utilized the galactose as the carbon source [47]. Table 4 showed effect lysine, isoleucine, glycine, thiamine, arginine, treptophan, proline, glutamic acid, cysteine, andmethionine on L-glutaminase production.…”
Section: Effect Of Different Nitrogen and Carbon Sources On L-glutamimentioning
confidence: 99%
“…L-glutamine at concentration of 2.5% supported the highest induction of L-glutaminase up 78.79 U/ml. The high yield of L-glutaminase (32.7 U/ml) produced by Streptomyces griseus when used L-glutamine as substrate due to L-glutamine is the specific inducers for L-glutaminase [47].…”
Section: Effect Of Different Concentrations Of L-glutamine On L-glutamentioning
confidence: 99%
See 1 more Smart Citation
“…Howevere, L-glutaminase was reported to be synthesized via bacteria [3], fungi [4], yeast [5], actinomycetes [6].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, no change in pH level was detected. Suresh Kumar et al (2013) reported that the production of L-glutaminase from Serratia marcescens was maximized at 0.75% NaCl. On the other hand, Krishnakumar et al (2011) and Abdallah et al (2013) found that the maximal L-glutaminase activities produced by marine alkalophilic Streptomyces sp.-SBU1 and Streptomyces avermitilis were observed in a medium supplemented with 2 and 3% NaCl (w/v), respectively.…”
Section: Effect Of Nacl Concentrationmentioning
confidence: 99%